Influence of Early Heat Conditioning and Betaine or Ammonium Chloride Supplementation on Performance and Physiological Parameters of Quail Chicks in Hot Climate - El-Moniary, Mosaad M.; Goud, Ahmed; Hamouda, Yasser; Youssef , Amani W.; Hassan, Hussein M.A. (International Journal of Poultry Science, 2019)
Objective: This study was designed to determine the effects of early heat conditioning and betaine or ammonium chloride supplementation on growth performance and physiological parameters of quail chicks in hot climate. Materials and Methods: A total of 600-one day old quail chicks were divided into two groups, the first served as a control (non-conditioning) and the second exposed to early age heat condition (40±1ºC for 24 h at the 5th day of age). Then each group were divided into three subgroups, the first was fed the basal diet and served as a control, the second was fed the basal diet supplemented with betaine (1.5 g kg–1) and the third was fed the basal diet supplemented with ammonium chloride (0.5 g kg–1). Results: The results at 40 day of age showed that early heat conditioning with or without addition significantly (p<0.05) improved body weight and feed conversion ratio. The best improvement on performance was recorded for birds exposed to early heat conditioning and fed betaine or ammonium chloride supplemented diet. Addition of either betaine or ammonium chloride to quail diets resulted in a significant (p<0.05) improvement of blood measurements. Exposing quail to early heat conditioning resulted in a significant improvement of total plasma proteins, plasma globulin and the level of thyroid hormones. Addition of either betaine or ammonium chloride has improved level of plasma protein fractions and antioxidant status compared to the control. Conclusion: It could be concluded that using early heat conditioning coupled with betaine or ammonium chloride supplementation gave more beneficial effects on performance and blood parameters.